2005
DOI: 10.1177/0731684405049862
|View full text |Cite
|
Sign up to set email alerts
|

Tensile, Flexural Properties of Unsaturated Polyester/Granite Powder and Unsaturated Polyester/Fly Ash Composites

Abstract: Composites are prepared using unsaturated polyester as the matrix and granite powder and fly ash as fillers. The tensile and flexural strengths of these composites are determined. The variation of tensile and flexural properties with weight fraction of the fillers is studied. The properties of granite powder composites are found to be better than those of fly ash composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Ramakrishna et al observed improvements in the tensile and flexural strengths in 40% FA‐filled 4% poly(methyl methacrylate)‐toughened epoxy matrix composites. Gupta et al reported an increase in the impact properties on the addition of FA in glass fiber/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Ramakrishna et al observed improvements in the tensile and flexural strengths in 40% FA‐filled 4% poly(methyl methacrylate)‐toughened epoxy matrix composites. Gupta et al reported an increase in the impact properties on the addition of FA in glass fiber/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Along with these, extensive research is going on to utilize fly ash as a filler in polymer matrix composites. Some researchers have reported their findings on fly ash filled polymer matrix composites [1][2][3][4][5][6][7][8][9][10][11]. Most of the studies reported are based on the mechanical, thermal, and electrical behavior of fly ash filled polymer matrix composites and a few reports are also available on the wear characteristics of such composites.…”
Section: Introductionmentioning
confidence: 99%
“…Kaushik et al 12 studied the mechanical properties and chemical resistance of short glass fiber-reinforced epoxy composites. Krishna et al 13 studied the tensile, impact, and chemical resistance properties of granite powder-epoxy composites. Sreenivasulu et al 14 studied the chemical resistance and tensile properties of short bamboo fiber-reinforced epoxy/poly carbonate composites.…”
Section: Introductionmentioning
confidence: 99%